2024
DOI: 10.1001/jamanetworkopen.2024.3354
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Telemedicine Use in the US, 2022

Eva Chang,
Robert B. Penfold,
Nancy D. Berkman

Abstract: ImportanceTelemedicine use was common during the COVID-19 pandemic, expanding many patients’ approaches to accessing health care. Of concern is whether telemedicine access was poorer among higher-needs and disadvantaged populations.ObjectiveTo assess patient characteristics associated with telemedicine use and telemedicine mode and describe telemedicine visit experiences by telemedicine mode.Design, Setting, and ParticipantsThis cross-sectional study included data from the 2022 Health Information National Tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…The prevalence of IMSU (39.43% with the provincial eld survey data) reported in our results was similar to the latest data reported in Health Information National Trends Survey (HINTS) in the U.S. (39.3%), and were consistent with prior literature on digital health inequities among patients with inferior demographic (e.g., gerontal patients) and socio-economic factors (e.g., educated at basic education level), as well as increased IMSU accessed among patients with poorer health status (e.g., suffering multi chronic diseases) , but not for gender in this study [13,20,25,[27][28][29][30]. We also found that, the respondents from the national online survey with superior demographic and socio-economic factors, but poorer health status than those from the provincial eld survey.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of IMSU (39.43% with the provincial eld survey data) reported in our results was similar to the latest data reported in Health Information National Trends Survey (HINTS) in the U.S. (39.3%), and were consistent with prior literature on digital health inequities among patients with inferior demographic (e.g., gerontal patients) and socio-economic factors (e.g., educated at basic education level), as well as increased IMSU accessed among patients with poorer health status (e.g., suffering multi chronic diseases) , but not for gender in this study [13,20,25,[27][28][29][30]. We also found that, the respondents from the national online survey with superior demographic and socio-economic factors, but poorer health status than those from the provincial eld survey.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that, Chinese patients were mostly limited to shallow IMS (e.g., minor disease, and routine visit) mainly provided by private platform and Internet hospital, regardless of the data from the provincial eld survey or the national online survey. However, the respondents with superior demographic (e.g., aged below 60 years old) and socio-economic factors (e.g., higher annual disposable income) from the national online survey were more likely to be deeply involved in IMSU (e.g., mental diseases: 374 times with 10.44%; telediagnosis: 378 times with 8.23%), which were consistent with previous studies [30][31][32][33][34]. Prior research has also indicated that the patterns of IMSU would be deepen in the patients with a chronic condition, nevertheless, in this study, patients suffering chronic diseases were less accessed to IMSU that those not suffering (35.59% vs. 40.56%) based on the provincial eld survey data, and patients suffering chronic diseases accessed to IMSU at a high frequency was lower than that at a low frequency (29.86% vs. 34.45%) based on the national online survey data [13,20,32,[35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 89%
“…Then, urgent needs during the first year of the COVID-19 pandemic created a surge of adoption and reduction in regulatory barriers to telemedicine [54][55][56]. Now that we are past the crisis period, health systems, providers, and patients are exploring how, when, and where to use telemedicine in service of multistakeholder outcomes [57,58]. Despite its widespread adoption, research acknowledges limitations in today's most prevalent telemedicine systems, which rely primarily on synchronous, interactive video sessions and chat capabilities [59].…”
Section: Extending Telemedicinementioning
confidence: 99%